Challenges of the Interiorization of Higher Education at the Binational Campus Oiapoque, Amapá (Research, Society and Development, 2022)
The Federal University of Amapá (UNIFAP) institutionalized the process of internalization of higher education in order to democratize access to higher education and reduce social and regional asymmetries. From this perspective, this study evaluated the challenges and limitations that hinder the regional development of the Binational Oiapoque Campus. The intellectual strategy was ensured by the method association with interference, since there was communication of variables under dependence relationship in the process of institutionalization of the Binational Campus of Oiapoque. Here, we conclude that UNIFAP plays a catalyst role in the process of citizen education, while enabling the social, economic, environmental, technological and cultural development of the Amazon region.